Five‐Membered Ruthenacycles: Ligand‐Assisted Alkyne Insertion into 1, 3‐N, S‐Chelated Ruthenium Borate Species. Issue 59 (17th September 2019) - Zafar, Mohammad; Ramalakshmi, Rongala; Pathak, Kriti; Ahmad, Asif; Roisnel, Thierry; Ghosh, Sundargopal
Abstract: Building upon previous work, the chemistry of [(η 6 ‐ p ‐cymene)Ru{P(OMe)2 OR}Cl2 ], (R=H or Me) has been extended with [H2 B(mbz)2 ] − (mbz=2‐mercaptobenzothiazolyl) using different Ru precursors and borate ligands. As a result, a series of 1, 3‐N, S‐chelated ruthenium borate complexes, for example, [(κ 2 ‐N, S‐L)PR3 Ru{κ 3 ‐H, S, S'−H2 B(L)2 }], (2 a –d and 2 a' –d' ; R=Ph, Cy, OMe or OPh and L=C5 H4 NS or C7 H4 NS2 ) and [Ru{κ 3 ‐H, S, S'‐H2 B(L)2 }2 ], (3 : L=C5 H4 NS, 3' : L=C7 H4 NS2 ) were isolated upon treatment of [(η 6 ‐ p ‐cymene)RuCl2 PR3 ], 1 a –d (R=Ph, Cy, OMe or OPh) with [H2 B(mp)2 ] − or [H2 B(mbz)2 ] − ligands (mp=2‐mercaptopyridyl). All the Ru borate complexes, 2 a –d and 2 a' –d' are stabilized by phosphine/phosphite and hemilabile N, S‐chelating ligands. Treatment of these Ru borate species, 2 a' –c' with various terminal alkynes yielded two different types of five‐membered ruthenacycle species, namely [PR3 {C7 H4 S2 ‐( E )‐N‐C=CH(R' )}Ru{κ 3 ‐H, S, S' −H2 B(L)2 }], (4 –4' ; R=Ph and R' =CO2 Me or C6 H4 NO2 ; L=C7 H4 NS2 ) and [PR3 {C7 H4 NS‐( E )‐S‐C=CH(R' )}Ru{κ 3 ‐H, S, S' −H2 B(L)2 }], (5 –5', 6 and 7 ; R=Ph, Cy or OMe and R' =CO2 Me or C6 H4 NO2 ; L=C7 H4 NS2 ). All these five‐membered ruthenacycle species contain an exocyclic C=C moiety, presumably formed by the insertion of a terminal alkyne into the Ru−N and Ru−S bonds. The new species have been characterized spectroscopically and the structures were further confirmed by single‐crystal X‐ray diffraction analysis. Theoretical studies and chemical‐bonding analyses established that charge transfer occurs from phosphorus to ruthenium center following the trend PCy3 3 3 3 . Abstract : Access to ruthenacycles : Thermolysis of ruthenium borate complexes having hemilabile N, S‐chelating ligand with terminal alkynes yielded five‐membered ring isomeric ruthenacycles containing exocyclic C=C unit.